Control law and actuator capacity effect on the dynamic performance of a hybrid mass damper; the case of rottweil tower - Koutsoloukas, Lefteris; Nikitas, Nikolaos; Aristidou, Petros; Meinhardt, Christian (My University, 2020)
This paper considers different vibration control options for a real high-rise tower subjected to real wind loading. To mitigate excessive responses, the tower utilizes a hybrid passive - active control system with a relatively small actuator capacity. Firstly, the methodology for establishing a reduced order numerical model of the tower from a finite element realization is presented. Subsequently, to deal with physical constraints, a Model Predictive Control (MPC) algorithm is employed and compared to a more conventional Linear Quadratic Regulator (LQR). In both cases, the algorithms managed to keep the dynamic displacements within the set desired limit. It was concluded that, the MPC had a better performance when compared to the LQR in terms of peak amplitudes at the expense though of energy.
Keywords: Active/Hybrid mass damper; Model predictive control; Structural dynamics; Tall buildings; Vibration mitigation